Diagnostic Performance of Ultrasonography in Detecting Fatty Liver Disease in Comparison with Fibroscan in People Suspected of Fatty Liver - Leila Kamali; Atoosa Adibi; Shadi Ebrahimian; Fahime Jafari; Mohsen Sharifi (Advanced Biomedical Research, 2019)
Background: Fatty liver disease is a common hepatic disorder that remains undiagnosed due to the high number of asymptomatic patients and lack of a proper noninvasive diagnostic tool. Liver biopsy, the gold standard of liver steatosis diagnosis, is an invasive method that can be replaced by fibroscan. Fibroscan can detect liver steatosis with high sensitivity and specificity, but it is not accessible around the world. In this study, we compared ultrasonography (US) as a cheap and accessible device with fibroscan method in detecting patients with liver steatosis. Materials and Methods: We enrolled 77 patients in this study. US and fibroscan were done in each patient at a single day. Liver steatosis stages were recorded using US and fibroscan. The diagnostic performance of US was calculated, using fibroscan as the reference method. Results: The sensitivity and specificity of US in detecting fatty liver disease using fibroscan as a standard method were 73% and 69%, respectively. Conclusion: Based on sensitivity and specificity achieved from US, this study suggests that ultrasound is a suitable method for detecting patients with liver steatosis obviating liver biopsy and fibroscan.